Cybersecurity – Attack and Defense Strategies : Counter modern threats and employ state-of-the-art tools and techniques to protect your organization against cybercriminals, 2nd Edition /: Counter modern threats and employ state-of-the-art tools and techniques to protect your organization against cybercriminals, 2nd Edition. (2019) - Diogenes, Yuri; Ozkaya, Erdal
No abstract available